Inflammation-Related Gene Polymorphisms Associated With Primary Immune Thrombocytopenia - Li, Ju; Ma, Sai; Shao, Linlin; Ma, Chunhong; Gao, Chengjiang; Zhang, Xiao-hui; Hou, Ming; Peng, Jun (Frontiers in Immunology, 2017)
Primary immune thrombocytopenia (ITP) is an acquired autoimmune disease characterized by a reduced platelet count and an increased risk of bleeding. Although immense research has improved our understanding of ITP, the pathogenesis remains unclear. Here, we investigated the involvement of 25 single nucleotide polymorphisms (SNPs) of the inflammation-related genes, including CD24, CD226, FCRL3, IL2, IRF5, ITGAM, NLRP3, CARD8, PTPN22, SH2B2, STAT4, TNFAIP3, and TRAF1, in the pathogenesis and treatment-response of ITP. We recruited 312 ITP inpatients and 154 healthy participants in this case-control study. Inflammation-related SNP genotyping was performed on the Sequenom MassARRAY iPLEX platform. The expression of TNFAIP3 mRNA was determined by quantitative real-time RT-PCR. All SNPs in healthy controls were consistent with Hardy-Weinberg equilibrium. Statistical analysis revealed that rs10499194 in TNFAIP3 was significantly associated with a decreased risk of ITP after Bonferroni multiple correction (codominant, CT vs. CC, OR = 0.431, 95% CI = 0.262-0.711, p = 0.001; dominant, TT/CT vs. CC, OR = 0.249, 95% CI = 0.141-0.440, p = 0.000). Besides, TNFAIP3 expression was significantly higher in patients with CT and pooled CT/TT genotypes compared with CC genotype (p = 0.001; p = 0.001). Interestingly, rs10499194 was also associated with corticosteroid-sensitivity (codominant, CT vs. CC, OR = 0.092, 95% CI = 0.021 - 0.398, p = 0.001; dominant, TT/CT vs. CC, OR = 0.086, 95% CI = 0.020 - 0.369, p = 0.001; allelic, T vs. C, OR = 0.088, 95% CI = 0.021 - 0.372, p = 0.001). Furthermore, no significant association was found between inflammation-related SNPs and the severity or refractoriness of ITP after Bonferroni multiple correction. Our findings suggest that rs10499194 may be a protective factor for susceptibility and corticosteroid-sensitivity in ITP patients.